(untitled) (Politeja, 2018)
Sport as an Element of European Identity in the Context of European Union Regulations Sport is one of the new areas of the Union’s competence, conferred by the Treaty of Lisbon. Provisions of Community law are used in sport activities carried on within the EU Member States only to a limited extent. However, in recent years, the growing interest of the European Union authorities in sport is more visible. It results mainly from the importance of competitive sports in social and economic development. The variety of legal solutions in different countries led the Community institutions to try to work out a number of obligatory solutions. The EU’s action concerning sport policy is to support and coordinate the activities of the Member States, the decisions however remain at the discretion of individual states. In another set of provisions of the European Union, sport is very often the subject of the so‑called soft law, which has almost no legally binding force or is weaker than the traditional law. It takes the form of guidelines and standards that the countries may introduce at their sole discretion. The main goal of this paper is to determine the extent to which sport policy guidelines for the European Union are reflected in the in the area of the creation of a European identity.